Enantioselective Construction of Sulfur‐Containing Tetrasubstituted Stereocenters via Asymmetric Functionalizations of α‐Sulfanyl Cyclic Ketones - Ye, Xueqian; Pan, Yongkai; Chen, Yunrong; Yang, Xiaoyu (Advanced synthesis & catalysis, 2020)
Asymmetric functionalizations of α‐sulfanyl cyclic ketones were realized via chiral phosphoric acid catalyzed enantioselective addition reactions with aldimines, azodicarboxylates and allenamides. A series of chiral organosulfur compounds possessing sulfur‐containing tetrasubstituted stereocenters were accessed via these methods, with excellent regioselectivities and high stereoselectivities.